2020
DOI: 10.1177/1945892420952262
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Leak Repair Simulation Model: Face, Content, and Construct Validation

Abstract: Background Cerebrospinal fluid leak (CSFL) repair simulation models are scarce; however, these models are valuable tools for skull base reconstruction surgery training. Objectives This study aims to assess the face, content, and construct validity of a CSFL repair simulation model. Method Eight novices (residents- PGY3) and eight experts have performed skull base reconstruction in multiple sites in twelve human cadaveric heads in simulated surgical environment. The experts completed a post-study 21-item questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…Christian et al 26 used a similar model but with intrathecal perfusion of fluorescein‐dyed saline to optimize visual feedback of successful repair. Lastly, AlQatahni et al 10 , 11 described a similar model using fluorescein‐dyed saline and conducted two studies to establish the feasibility as well as face, content, and construct validity of their model.…”
Section: Resultsmentioning
confidence: 99%
“…Christian et al 26 used a similar model but with intrathecal perfusion of fluorescein‐dyed saline to optimize visual feedback of successful repair. Lastly, AlQatahni et al 10 , 11 described a similar model using fluorescein‐dyed saline and conducted two studies to establish the feasibility as well as face, content, and construct validity of their model.…”
Section: Resultsmentioning
confidence: 99%
“…Donoho et al perfused cadavers with artificial blood and demonstrated face and construct validity, as well as utility as an educational tool ( 23 , 34 ). Other cadaveric studies have looked at simulating CSF leak repair and demonstrated face, content and construct validity ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Simulation in neuro-otology was captured in 20 models (Supplemental Table 1). 10-30 Eight were intended for myringotomy +/− pressure equalization tube (PET) insertion, 7 for mastoidectomy, 2 for temporal bone dissection, one each for otoplasty, ossiculoplasty, and endoscopic transcanal tympanoplasty. Of the bench-top models, the myringotomy and PET insertion model described by Malekzadeh et al is notable for its low cost and low fidelity approach that incorporated readily available clinical supplies to enhance time to completion and global rating scores when compared to didactic training alone.…”
Section: State Of Simulation In Otolaryngology—head and Neck Surgerymentioning
confidence: 99%